Longevity Pathways (mTOR, SIRT, Insulin/IGF-1) as Key Modulatory Targets on Aging and Neurodegeneration - Henrique Mazucanti, Caio; Victor Cabral-Costa, Joao; Rodrigues Vasconcelos, Andrea; Zukas Andreotti, Diana; Scavone, Cristoforo; Mitiko Kawamoto, Elisa (Current Topics in Medicinal Chemistry, 2015)
Recent data from epidemiologic studies have shown that the majority of the public health costs are related to age-related disorders, and most of these diseases can lead to neuronal death. The specific signaling mechanisms underpinning neurodegeneration and aging are incompletely understood. Much work has been directed to the search for the etiology of neurodegeneration and aging and to new therapeutic strategies, including not only drugs but also non-pharmacological approaches, such as physical exercise and low-calorie dietary intake. The most important processes in aging-associated conditions, including neurodegeneration, include the mammalian (or mechanistic) target of rapamycin (mTOR), sirtuin (SIRT) and insulin/insulin growth factor 1 signaling (IIS) pathways. These longevity pathways are involved in an array of different processes, including metabolism, cognition, stress response and brain plasticity. In this review we focus on the current advances involving the mTOR, SIRT and IIS longevity pathways during the course of healthy aging processes and neurodegenerative diseases, bringing new insights in the form of a better understanding of the signaling mechanisms underpinning neurodegeneration and how these differ from physiological normal aging processes. This also provides new targets for the therapeutic management and/or prevention of these devastating age-related disorders.
Keywords: Insulin